Preparation method of refined coke powder and high-purity isostatic pressing graphite
By performing high-temperature halogen removal treatment on the raw materials for isostatic graphite production, combined with a high-temperature graphitization process, the problem of high impurity content inside isostatic graphite was solved, achieving the preparation of high-purity isostatic graphite and improving the uniformity and corrosion resistance of the material.
Patent Information
- Application Number
- CN202511471024.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2045-10-15
AI Technical Summary
In existing isostatic graphite production technology, it is difficult to control the impurity content, especially the high content of impurity elements inside large-size, large-volume graphite blanks, which leads to low yield of semiconductor devices and short material life.
At the source of production, the asphalt coke or petroleum coke raw materials are subjected to high-temperature halogen removal treatment to prepare refined coke powder. Combined with the high-temperature graphitization process, impurities are removed by continuous heating and Freon gas to reduce impurity content, improve powder particle morphology and kneading effect, and finally prepare high-purity isostatic graphite.
The internal impurity content of high-purity isostatic graphite was reduced to less than 20 ppm, which improved the uniformity and corrosion resistance of graphite materials, and increased the yield of devices and the lifespan of materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to semiconductor device manufacturing technology, and in particular to a method for preparing refined coke powder and high-purity isostatic graphite. Background Technology
[0002] High-purity isostatic graphite possesses excellent electrical and thermal conductivity, high-temperature resistance, and good chemical stability, making it a key material in high-end manufacturing industries such as semiconductors, solar photovoltaics, and aerospace. In particular, many manufacturing processes in the semiconductor industry take place in high-temperature and corrosive environments, placing stringent requirements on the purity and corrosion resistance of the equipment and materials used in these processes. High-purity graphite, as an important auxiliary material in semiconductor manufacturing, is a crucial factor in determining product quality.
[0003] Current isostatic graphite production technology typically uses pitch coke or petroleum coke as raw materials. After grinding, pitch is added as a binder for mixing, followed by processes such as rolling, secondary grinding, molding, calcination, impregnation, and graphitization to obtain isostatic graphite. The resulting isostatic graphite undergoes precision machining and then high-temperature chemical purification using specialized equipment to obtain high-purity / ultra-high-purity isostatic graphite products.
[0004] Although existing high-purity isostatic graphite production technologies use calcined coke with low impurity content as raw material, the impurity content is still around 0.5%, and other impurities may be introduced during calcination, storage, and packaging. Furthermore, the crushing and conveying processes during isostatic graphite production can introduce metallic impurities, resulting in a high impurity element content in the pressed raw product. While high-temperature and halogen gas-thermal purification in subsequent graphitization processes can significantly remove impurity elements from the green body, the high-purity isostatic graphite used for semiconductor applications is produced using fine-particle or even ultra-fine-particle processes, resulting in high green body density. This limits the penetration effect of halogen gas into the interior of the green body during purification, leading to a significant difference in purification effects between the surface and core layers. Especially for large-format, high-volume isostatically pressed graphite preforms, the impurity element content on the surface can be reduced to below 50 ppm after gas-thermal purification, but the impurity element content inside the preform can exceed 200 ppm. In this case, the machined product needs to undergo secondary or even multiple high-temperature chemical purification processes to bring the surface impurity element content down to below 10 ppm. However, with increasing usage time in high-temperature corrosive environments, impurities inside the material will still diffuse to the surface, affecting device yield and the lifespan of the graphite material.
[0005] Therefore, this invention proposes a method for preparing refined coke powder and high-purity isostatic graphite to solve the above problems. This is of great significance for meeting the requirements of the semiconductor and electronics industries for the uniformity and high / ultra-high purity of graphite materials. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for preparing refined coke powder and high-purity isostatic graphite.
[0007] To solve the technical problem, the solution of the present invention is:
[0008] Firstly, a method for preparing refined coke powder is provided, including:
[0009] (1) Using calcined petroleum coke or calcined pitch coke as raw material, after crushing and grinding, coke primary powder with a particle size D50 of 5~25μm is obtained;
[0010] (2) Add the coke powder to a graphite crucible and then transfer it to a graphitization furnace for high-temperature halogen removal treatment; heat it continuously to 2300~2500℃ and maintain it for 2~6 hours, then stop heating and cool down; during this process, start to continuously introduce Freon gas when the temperature reaches 1800~1900℃, and stop introducing gas when the temperature drops to 2200℃; after cooling to room temperature, obtain impurity-free coke powder with impurity content <0.01%;
[0011] (3) The impurity-removed coke powder is fed into a fluidized bed air jet mill for dispersion, grinding and shaping; after air jet classification and magnetic separation, refined coke powder with D50 of 5~25μm is obtained.
[0012] As a preferred embodiment of the present invention, in step (1), the quality of calcined pitch coke or calcined petroleum coke should meet the following requirements: impurity content < 0.5%, volatile matter < 0.5%, sulfur content < 0.5%, and carbon content > 99.5%.
[0013] As a preferred embodiment of the present invention, in step (1), the raw material is first crushed to a particle size of less than 5 mm using a double roller crusher, and then the particles are ground using a vertical roller mill.
[0014] As a preferred embodiment of the present invention, in step (2), the heating rate of the graphitization furnace is 5~25℃ / hour.
[0015] As a preferred embodiment of the present invention, in step (2), the coke powder is weighed before loading into the furnace, and Freon is introduced at 0.2-0.8% of its weight.
[0016] As a preferred embodiment of the present invention, in step (2), after heating is stopped, the crucible is cooled to 150~200°C by natural cooling, and then removed from the graphitization furnace and further cooled to room temperature by natural cooling.
[0017] As a preferred embodiment of the present invention, in step (3), the impurity-removed coke powder is first transported from the crucible to the storage bin for temporary storage using a negative pressure conveying system, and then transported to the fluidized bed air jet mill for air jet classification according to the feeding requirements.
[0018] As a preferred embodiment of the present invention, in step (3), a magnetic separation system is used for magnetic separation; the magnetic separation system is equipped with at least 3 stages of iron removers, and each stage of iron remover is composed of permanent magnets with a magnetic force exceeding 12000GS.
[0019] This invention further provides a method for preparing high-purity isostatic graphite from the refined coke powder obtained by the aforementioned method, comprising:
[0020] (1) Take refined coke powder and high-temperature coal tar pitch with impurity content <0.05% in a weight ratio of 0.8~1.0:1.0~1.6; first add the refined coke powder to the carbon kneader and preheat it to 150°C, then add the melted high-temperature coal tar pitch, and obtain a paste by kneading; take out the paste, and obtain pressed powder by cooling, crushing, secondary grinding and sieving.
[0021] (2) The powder is filled into the mold and pressed into shape by a cold isostatic press to obtain the raw product; the raw product is subjected to a first roasting, impregnation, second roasting and high temperature graphitization treatment to obtain high purity isostatic graphite with internal impurity content <20ppm.
[0022] As a preferred embodiment of the present invention, during the high-temperature graphitization treatment after secondary calcination, the maximum temperature of 2800~3000℃ is gradually reached in a stepped manner: the temperature is increased to 500℃ at a rate of 20℃ / h, to 1500℃ at a rate of 5~10℃ / h, to 1800℃ at a rate of 7~10℃ / h, to 2400℃ at a rate of 10~15℃ / h, and to the maximum temperature at a rate of 15~20℃ / h; when the temperature reaches 1800℃, Freon gas is introduced, and the amount of gas introduced per ton of product is calculated based on the weight of the product charged into the furnace, which is 10~25kg. The gas introduction continues until the temperature drops to 2200℃ during the cooling phase.
[0023] Description of the invention principle:
[0024] Currently, manufacturers using pitch coke or petroleum coke as raw materials to produce isostatic graphite typically use halogens (chlorine, Freon, etc.) to purify the graphite products, and this purification usually requires high-temperature conditions. Therefore, to save energy and reduce costs, purification is often combined with graphitization, usually placed as the final step in the entire process. That is, during the high-temperature graphitization of the raw product, chlorine and / or Freon gases are introduced to simultaneously oxidize and purify impurities, achieving the purpose of impurity removal. However, this inevitably leads to a significant difference in purification effects between the surface and the core of the product. Furthermore, based on existing production experience, technicians generally believe that if pitch coke or petroleum coke is subjected to high-temperature impurity removal beforehand, it will alter the properties of the raw materials, resulting in lower performance indicators after graphitization, making it difficult to meet usage requirements. Therefore, despite years of continuous optimization of the isostatic graphite production process, industry professionals' understanding of this point has not changed substantially. Even in the relevant technical solutions recorded in the patent documents of the last two years, the process or procedure is still followed, such as CN116444274 A, CN117024146 A, CN119430939A, etc.
[0025] This invention innovatively proposes to first purify and remove impurities from the raw material powder at the source of production, thereby producing highly pure refined coke powder. This powder is then used in the kneading process, which can maximize the uniformity of the paste and the finished product, maintaining consistency throughout. This avoids the problems of inconsistent impurity removal between the surface and the interior of the embryo, and the diffusion of impurities to the outer layer after long-term use of the finished product, which are present in traditional processes.
[0026] Through long-term observation and analysis, the applicant discovered that the grinding process for pitch coke or petroleum coke raw materials is the most challenging in the production process of isostatic graphite. Compared to the secondary grinding process for the mixed paste, the grinding of pitch coke or petroleum coke raw materials often introduces the largest amount of metallic impurities in the entire production process. Therefore, this invention employs a rapid high-temperature impurity removal technology (direct continuous heating rather than a stepped heating method) for primary coke powder, and controls the maximum temperature during impurity removal to be slightly lower than the graphitization temperature for the raw product, achieving high-temperature chemical impurity removal while preserving the original properties of the coke. This invention utilizes this treatment method to eliminate the source of the largest metallic impurities at the source, thus overcoming a long-standing technical challenge for engineers. Combined with the final stage of graphitization treatment for the raw product, impurities introduced into the surface of the secondary-calcined product in later processes can be further treated, thereby obtaining a high-purity isostatic graphite product.
[0027] Compared with the prior art, the technical advantages of the present invention are:
[0028] 1. In existing technologies, the primary coke powder used in the kneading process often has an impurity content exceeding 0.5% due to the lack of high-temperature impurity removal treatment. However, the primary coke powder prepared by this invention has an impurity content of <0.01%, thus significantly reducing the impurity content from the raw material stage. Furthermore, combined with the final high-temperature graphitization process, it avoids the large amount of metallic impurities generated during the crushing and grinding of calcined petroleum coke or calcined pitch coke raw materials, which are located below the surface of the green product (bulk) and cannot be eliminated during graphitization. Therefore, the preparation process of this invention can achieve a high purity index of <20ppm for the final graphite product, far lower than products obtained by conventional processes.
[0029] 2. This invention, after subjecting primary coke powder to high-temperature halogen removal treatment, further improves the particle morphology of the powder through airflow shaping, achieving a higher tap density. This promotes the wetting of the coke powder by the asphalt during the mixing process, resulting in better mixing performance. Compared with existing technologies, the raw product obtained by this invention has a higher bulk density (by more than 0.05 g / cm³), a higher bulk density (by more than 0.03 g / cm³) for the graphite material, and a higher flexural strength (by more than 5 MPa), all showing significant improvements.
[0030] 3. This invention reduces the micropores remaining due to the volatilization of thermochemical purification gases during the final stage of graphitization in traditional processes by subjecting primary coke powder to high-temperature halogen removal treatment; thus, it can reduce the porosity of isostatic graphite products and effectively improve the microstructure of graphite materials.
[0031] 4. In this invention, during the high-temperature halogen removal treatment of primary coke powder, the microcrystalline structure in the coke particles is further grown, which is beneficial to the graphitization transformation of the secondary roasted product during the graphitization heat treatment process, and can effectively improve the corrosion resistance of graphite materials. Compared with existing isostatic graphite preparation technology, the isostatic graphite prepared by this invention has a lower oxidation weight loss rate after heat treatment at 600℃ for 30 hours in an air atmosphere. Detailed Implementation
[0032] The specific embodiments of the present invention will be described in detail below.
[0033] I. Overview of the Technical Solution of the Invention
[0034] 1. The method for preparing refined coke powder in this invention includes:
[0035] (1) Using calcined petroleum coke or calcined pitch coke as raw material, first use a double roller crusher to crush the raw material to a particle size of less than 5 mm, and then use a vertical roller mill to grind the particles to obtain coke powder with a particle size D50 of 5~25 μm; wherein, the quality of calcined pitch coke or calcined petroleum coke should meet the following requirements: impurity content <0.5%, volatile matter <0.5%, sulfur content <0.5%, and carbon content >99.5%.
[0036] (2) After weighing the primary coke powder, add it to a graphite crucible and then transfer it to a graphitization furnace for high-temperature halogen removal treatment. The heating rate is 5~25℃ / hour. When the temperature reaches 1800~1900℃, start continuously introducing Freon gas at 0.2~0.8% of the weight of the primary coke powder. After heating to the maximum temperature of 2300~2500℃, maintain it for 2~6 hours. After stopping the heating, cool it by natural heat dissipation. Stop introducing Freon when the temperature drops to 2200℃. When the temperature drops to 150~200℃, the crucible can be removed from the graphitization furnace and further cooled naturally to room temperature to obtain impurity-removed coke powder with an impurity content of <0.01%.
[0037] (3) The impurity-removed coke powder is fed into a fluidized bed air jet mill for dispersion, grinding and shaping; after air jet classification and magnetic separation, refined coke powder with D50 of 5~25μm is obtained.
[0038] First, the cooled, impurity-removed coke powder is transported from the crucible to a storage silo for temporary storage using a negative pressure conveying system. Then, it is conveyed to a fluidized bed jet mill for air classification according to the feeding requirements. Specifically, a magnetic separation system can be used for magnetic separation. The magnetic separation system is equipped with at least three stages of iron separators, each of which consists of permanent magnets with a magnetic force exceeding 12000GS.
[0039] 2. A method for further preparing high-purity isostatic graphite using refined coke powder, including:
[0040] (1) Take refined coke powder and high-temperature coal tar pitch with impurity content <0.05% in a weight ratio of 0.8~1.0:1.0~1.6; first add the refined coke powder to the carbon kneader and preheat it to 150°C, then add the melted high-temperature coal tar pitch, and obtain a paste by kneading; take out the paste, and obtain pressed powder by cooling, crushing, secondary grinding and sieving.
[0041] (2) The powder is filled into the mold and pressed into shape by a cold isostatic press to obtain the raw product; the raw product is subjected to a first roasting, impregnation, second roasting and high temperature graphitization treatment to obtain high purity isostatic graphite with internal impurity content <20ppm.
[0042] During the high-temperature graphitization process, the maximum temperature of 2800~3000℃ is gradually reached in a stepped manner: the temperature is increased to 500℃ at a rate of 20℃ / h, to 1500℃ at a rate of 5~10℃ / h, to 1800℃ at a rate of 7~10℃ / h, to 2400℃ at a rate of 10~15℃ / h, and finally to the maximum temperature at a rate of 15~20℃ / h. When the temperature reaches 1800℃, Freon gas is introduced. Based on the weight of the product loaded into the furnace, the amount of gas introduced per ton of product is calculated to be 10~25 kg. Gas introduction continues until the temperature drops to 2200℃ during the cooling phase. The cooling process is natural cooling, and the product is removed from the furnace after cooling to 200℃, yielding high-purity isostatic graphite.
[0043] This invention does not specifically limit other process parameters or treatment measures in the isostatic graphite production process; they can be controlled according to conventional process conditions. For example, the cooling, crushing, secondary grinding, and sieving of the paste; the pressing of the powder into raw products using a cold isostatic press; and the primary roasting, impregnation, and secondary roasting of the raw products can all be carried out according to conventional process conditions commonly used in the industry.
[0044] II. Specific Implementation Examples and Comparative Examples
[0045] Example 1
[0046] 1) Use a double roll crusher to crush calcined pitch coke with impurity content <0.5%, volatile matter <0.5%, sulfur content <0.5%, and carbon content >99.5% to less than 5mm, and then use a vertical roller mill to grind it to obtain coke primary powder with a particle size D50 of 25μm, a loose density of 0.51g / cm³, and a tapped density of 0.85g / cm³;
[0047] 2) The primary coke powder is loaded into a graphite crucible and placed in a single-unit graphitization furnace; the temperature is increased to 2500℃ at a heating rate of 5℃ / hour and held for 6 hours; then heating is stopped and the temperature is allowed to cool naturally to below 200℃ before being removed from the furnace for further cooling. During this process, when the temperature reaches 1900℃, Freon gas is continuously introduced at a rate of 0.8% of the weight of the primary coke powder, and this gas introduction is stopped when the temperature reaches 2200℃ during the cooling phase. After the impurity-removed coke powder cools to below 50℃, it is sent to a storage silo using a negative pressure suction device. The impurity content in the resulting impurity-removed coke powder is 0.0035%.
[0048] 3) The impurity-removed coke powder is dispersed, pulverized and shaped using a fluidized bed air jet mill. The pulverizing air pressure is 0.8 MPa. Then, the coke powder is obtained by air jet classification and sorting with a particle size D50 of 25 μm, a loose density of 0.51 g / cm³ and a tapped density of 0.85 g / cm³.
[0049] 4) The obtained coke powder is fed into a magnetic separation system consisting of three rotary iron removers for magnetic separation and impurity removal, thereby obtaining refined coke powder for the production of high-purity isostatic graphite; the median particle size D50 of the refined coke powder is 25μm, the tap density is 0.85g / cm³, and the impurity content is 0.0025%.
[0050] 5) The obtained refined coke powder is put into a carbon-specific kneading pot and mixed evenly and preheated to 150°C. Then, liquid high-temperature coal tar pitch with a softening point of 95°C and an impurity content of <0.05% is added according to the weight ratio of refined coke powder to high-temperature coal tar pitch of 1.0:1.6. After kneading for 60 minutes, the mixture is removed from the pot and cooled to obtain a paste. After the paste is cooled to 50°C, it is cooled, crushed, ground twice and screened to obtain pressed powder.
[0051] 6) After loading the powder into a rubber mold and sealing it, vacuum the air out and load it into a cold isostatic press. Increase the pressure to 80 MPa at a rate of 1 MPa / s and hold for 4 minutes. Then increase the pressure to 150 MPa at a rate of 0.8 MPa / s and hold for 10 minutes. Then decrease the pressure to 100 MPa at a rate of 0.5 MPa / s and hold for 5 minutes. Finally, release the pressure at a rate of 1 MPa / s. After demolding, a raw product with a bulk density of 1.52 g / cm³ is obtained.
[0052] 7) The raw product is loaded into the roasting tank and filled with filler with good thermal conductivity. Then it is loaded into the roasting furnace and purged with nitrogen gas to maintain a positive pressure of 0.5 kPa in the furnace. The temperature is then increased to 200℃ at a rate of 8.0℃ / h and held for 10h. The temperature is then increased to 900℃ at a rate of 5.0℃ / h and held for 20h. The temperature is then decreased to 80℃ at a rate of 6.0℃ / h and removed from the furnace. After cooling to room temperature, the product is taken out of the roasting tank to obtain the first roasted product.
[0053] 8) After preheating the calcined product to 280℃, it is placed into an impregnation tank. The air inside the impregnation tank is evacuated and then liquid impregnation bitumen with a softening point of 80℃ is injected for pressure impregnation. The maximum impregnation pressure is 2.0MPa, and the impurity content of the impregnation bitumen used is <0.05%.
[0054] 9) After impregnation, the product is placed in a roasting furnace, covered with filler with good thermal conductivity, and heated to the maximum temperature of 800℃. The heating rate from room temperature to 400℃ is 8℃ / h, then it is held at 400℃ for 10h, the heating rate from 400℃ to 800℃ is 5℃ / h, and it is held at 800℃ for 15h. After that, it is naturally cooled to 100℃ and then removed from the furnace to obtain the second roasted product.
[0055] 10) The secondary-calcined product is loaded into the Atchison graphitization furnace and heated to 3000℃ for graphitization treatment. The heating rate is 20℃ / h to 500℃, 7℃ / h to 1500℃, 10℃ / h to 1800℃, 15℃ / h to 2400℃, and 20℃ / h to the highest temperature. During the heating process, Freon gas is introduced when the temperature reaches 1800℃ and is stopped when the temperature drops to 2200℃. The amount of gas introduced per ton of product is calculated based on the weight of the product loaded into the furnace. The product is then allowed to cool naturally to 200℃ before being removed from the furnace to obtain high-purity isostatic graphite.
[0056] According to relevant national product quality standards, the high-purity isostatic graphite product was tested and found to have the following characteristics: internal impurity content 12 ppm, porosity 8.7%, bulk density 1.81 g / cm³, flexural strength 58 MPa, and oxidation weight loss rate 4.2%.
[0057] Example 2
[0058] 1) Use a double roll crusher to crush calcined petroleum coke with impurity content <0.5%, volatile matter <0.5%, sulfur content <0.5%, and carbon content >99.5% to less than 5mm, and then use a vertical roller mill to grind it into coke powder with a particle size D50 of 5μm, a loose density of 0.31g / cm³, and a tapped density of 0.63g / cm³.
[0059] 2) The primary coke powder is loaded into a graphite crucible and placed in a single-unit graphitization furnace; the temperature is increased to 2300℃ at a heating rate of 25℃ / hour and held for 2 hours; then heating is stopped and the temperature is allowed to cool naturally to below 150℃ before being removed from the furnace for further cooling. During this process, when the temperature reaches 1800℃, Freon gas is continuously introduced at a rate of 0.2% of the weight of the primary coke powder, and this gas introduction is stopped when the temperature reaches 2200℃ during the cooling phase. After the impurity-removed coke powder cools to below 50℃, it is sent to a storage silo using a negative pressure suction device. The impurity content in the resulting impurity-removed coke powder is 0.0062%.
[0060] 3) The impurity-removed coke powder is dispersed, pulverized and shaped using a fluidized bed air jet mill. The pulverizing air pressure is 0.8 MPa. Then, the coke powder is obtained by air jet classification and sorting with a particle size D50 of 5 μm, a loose density of 0.31 g / cm³ and a tapped density of 0.63 g / cm³.
[0061] 4) The obtained coke powder is fed into a magnetic separation system consisting of three rotary iron removers for magnetic separation and impurity removal, thereby obtaining refined coke powder for the production of high-purity isostatic graphite; the median particle size D50 of the refined coke powder is 5μm, the loose packing density is 0.31g / cm³, the tapped density is 0.63g / cm³, and the impurity content is 0.0030%.
[0062] 5) The obtained refined coke powder is put into a carbon-specific kneading pot and mixed evenly and preheated to 150°C. Then, liquid high-temperature coal tar pitch with a softening point of 95°C and an impurity content of <0.05% is added according to the weight ratio of refined coke powder to high-temperature coal tar pitch of 0.8:1.0. After kneading for 60 minutes, the mixture is removed from the pot and cooled to obtain a paste. After the paste is cooled to 50°C, it is cooled, crushed, ground twice and screened to obtain pressed powder.
[0063] 6) After loading the powder into a rubber mold and sealing it, vacuum the air out and load it into a cold isostatic press. Increase the pressure to 100 MPa at a rate of 1 MPa / s and hold for 4 minutes. Then increase the pressure to 160 MPa at a rate of 0.8 MPa / s and hold for 20 minutes. Then decrease the pressure to 120 MPa at a rate of 0.5 MPa / s and hold for 5 minutes. Then decrease the pressure to 80 MPa at a rate of 0.8 MPa / s. Finally, release the pressure at a rate of 1 MPa / s. After demolding, a raw product with a bulk density of 1.55 g / cm³ is obtained.
[0064] 7) The raw product is loaded into the roasting tank and filled with filler with good thermal conductivity. Then it is loaded into the roasting furnace and purged with nitrogen gas to maintain a positive pressure of 0.5 kPa in the furnace. The temperature is then increased to 200℃ at a rate of 5.0℃ / h and held for 20h. The temperature is then increased to 900℃ at a rate of 2.0℃ / h and held for 40h. The temperature is then decreased to 80℃ at a rate of 5.0℃ / h and removed from the furnace. After cooling to room temperature, the product is taken out of the roasting tank to obtain the first roasted product.
[0065] 8) After the product is preheated to 280°C after one firing, it is placed into an impregnation tank. The air inside the impregnation tank is evacuated and then liquid impregnation bitumen with a softening point of 80°C is injected for pressure impregnation. The maximum impregnation pressure is 3.5 MPa, and the impurity content of the impregnation bitumen used is <0.05%.
[0066] 9) After impregnation, the product is placed in a roasting furnace, covered with filler with good thermal conductivity, and heated to the maximum temperature of 800℃. The heating rate from room temperature to 400℃ is 8℃ / h, then it is held at 400℃ for 20h, the heating rate from 400℃ to 800℃ is 4℃ / h, and it is held at 800℃ for 20h. After that, it is naturally cooled to 100℃ and then removed from the furnace to obtain the second-roasted product.
[0067] 10) The secondary-calcined product is loaded into the Atchison graphitization furnace and heated to 2800℃ for graphitization treatment. The heating rate is 20℃ / h to 500℃, 5℃ / h to 1500℃, 7℃ / h to 1800℃, 10℃ / h to 2400℃, and 15℃ / h to the maximum temperature of 2800℃. During the heating process, Freon gas is introduced when the temperature reaches 1800℃ and is stopped when the temperature drops to 2200℃. The amount of gas introduced per ton of product is calculated based on the weight of the product loaded into the furnace. The product is then allowed to cool naturally to 200℃ before being removed from the furnace to obtain high-purity isostatic graphite.
[0068] According to relevant national product quality standards, the high-purity isostatic graphite product was tested and found to have the following characteristics: internal impurity content 18 ppm, porosity 6.5%, bulk density 1.88 g / cm³, flexural strength 65 MPa, and oxidation weight loss rate 3.3%.
[0069] Example 3
[0070] 1) Use a double roll crusher to crush calcined petroleum coke with impurity content <0.5%, volatile matter <0.5%, sulfur content <0.5%, and carbon content >99.5% to less than 5mm, and then use a vertical roller mill to grind it into coke powder with a particle size D50 of 12μm, a loose density of 0.40g / cm³, and a tapped density of 0.78g / cm³.
[0071] 2) The primary coke powder is loaded into a graphite crucible and placed in a single-unit graphitization furnace. The furnace is heated to 2350℃ at a rate of 12℃ / hour and held for 3 hours. Heating is then stopped, and the coke is allowed to cool naturally to below 180℃ before being removed from the furnace and allowed to continue cooling. During this process, when the temperature reaches 1850℃, Freon gas is continuously introduced at a rate of 0.4% of the weight of the primary coke powder, continuing until the temperature reaches 2200℃ during the cooling phase, at which point the gas introduction is stopped. After the purified coke powder cools to below 50℃, it is transported to a storage silo using a negative pressure suction device. The resulting purified coke powder contains 0.0050% impurities.
[0072] 3) The impurity-removed coke powder is dispersed, pulverized and shaped using a fluidized bed air jet mill. The pulverizing air pressure is 0.8 MPa. Then, the coke powder is obtained by air jet classification and sorting with a particle size D50 of 12 μm, a loose density of 0.40 g / cm³ and a tapped density of 0.78 g / cm³.
[0073] 4) The obtained coke powder is fed into a magnetic separation system consisting of three rotary iron removers for magnetic separation and impurity removal, thereby obtaining refined coke powder for the production of high-purity isostatic graphite; the median particle size D50 of the refined coke powder is 12μm, the loose packing density is 0.40g / cm³, the tapped density is 0.78g / cm³, and the impurity content is 0.0020%.
[0074] 5) The obtained refined coke powder is put into a carbon-specific kneading pot and mixed evenly and preheated to 150°C. Then, liquid high-temperature coal tar pitch with a softening point of 95°C and an impurity content of <0.05% is added according to the weight ratio of refined coke powder to high-temperature coal tar pitch of 0.9:1.5. After kneading for 60 minutes, the mixture is removed from the pot and cooled to obtain a paste. After the paste is cooled to 50°C, it is cooled, crushed, ground twice and screened to obtain pressed powder.
[0075] 6) After loading the powder into a rubber mold and sealing it, vacuum the air out and load it into a cold isostatic press. Increase the pressure to 80 MPa at a rate of 1 MPa / s and hold for 4 minutes. Then increase the pressure to 150 MPa at a rate of 0.8 MPa / s and hold for 10 minutes. Then decrease the pressure to 100 MPa at a rate of 0.5 MPa / s and hold for 5 minutes. Finally, release the pressure at a rate of 1 MPa / s. After demolding, a raw product with a density of 1.54 g / cm³ is obtained.
[0076] 7) The raw product is loaded into the roasting tank and filled with filler with good thermal conductivity. Then it is loaded into the roasting furnace and purged with nitrogen gas to maintain a positive pressure of 0.5 kPa in the furnace. The temperature is then increased to 200℃ at a rate of 8.0℃ / h and held for 6 hours. The temperature is then increased to 900℃ at a rate of 3.5℃ / h and held for 15 hours. The temperature is then decreased to 80℃ at a rate of 5.0℃ / h and removed from the furnace. After cooling to room temperature, the product is taken out of the roasting tank to obtain the first roasted product.
[0077] 8) After the product is preheated to 280°C after one firing, it is placed in an impregnation tank. The air inside the impregnation tank is evacuated and then liquid impregnation bitumen with a softening point of 80°C is injected for pressure impregnation. The maximum impregnation pressure is 2.0 MPa, and the impurity content of the impregnation bitumen used is <0.05%.
[0078] 9) After impregnation, the product is placed in a roasting furnace, covered with filler with good thermal conductivity, and heated to the maximum temperature of 800℃. The heating rate from room temperature to 400℃ is 8℃ / h, then it is held at 400℃ for 10h, the heating rate from 400℃ to 800℃ is 5℃ / h, and it is held at 800℃ for 15h. After that, it is naturally cooled to 100℃ and then removed from the furnace to obtain the second roasted product.
[0079] 10) The secondary-calcined product is loaded into the Atchison graphitization furnace and heated to 2850℃ for graphitization treatment. The heating rate is 20℃ / h to 500℃, 10℃ / h to 1500℃, 8℃ / h to 1800℃, 12℃ / h to 2400℃, and 16℃ / h to the highest temperature. During the heating process, Freon gas is introduced when the temperature reaches 1800℃ and is stopped when the temperature drops to 2200℃. Based on the weight of the product loaded into the furnace, the amount of gas introduced per ton of product is 18kg. After cooling naturally to 200℃, the product is removed from the furnace to obtain high-purity isostatic graphite.
[0080] According to relevant national product quality standards, the high-purity isostatic graphite product was tested and found to have the following characteristics: internal impurity content 15 ppm, porosity 8.0%, bulk density 1.82 g / cm³, flexural strength 59 MPa, and oxidation weight loss rate 4.5%.
[0081] Comparative Example 1
[0082] In this comparative example, the primary coke powder was not subjected to high-temperature impurity removal treatment. Instead, it was directly used after grinding for conventional processes such as mixing, molding, calcination, impregnation, and graphitization to produce isostatic graphite. These processes and control parameters are the same as in Example 1, as detailed below:
[0083] 1) Calcined pitch coke with impurity content <0.5%, volatile matter <0.5%, sulfur content <0.5%, and carbon content >99.5% is crushed to below 5mm, and then ground into powder using a vertical roller mill to obtain primary coke powder with a particle size D50 of 25μm, a loose density of 0.51g / cm³, and a tapped density of 0.85g / cm³, and an impurity content of 0.5200%.
[0084] 2) The obtained coke powder is put into a carbon-specific kneading pot and mixed evenly and preheated to 150°C. Then, liquid high-temperature coal tar pitch with a softening point of 95°C and an impurity content of <0.05% is added according to the weight ratio of refined coke powder to high-temperature coal tar pitch of 1.0:1.6 and kneaded for 60 minutes. After kneading, the mixture is removed from the pot and cooled to obtain a paste. After the paste is cooled to 50°C, it is ground again to obtain pressed powder.
[0085] 3) After loading the powder into a rubber mold and sealing it, vacuum the air out and load it into a cold isostatic press. Increase the pressure to 80 MPa at a rate of 1 MPa / s and hold for 4 minutes. Then increase the pressure to 150 MPa at a rate of 0.8 MPa / s and hold for 10 minutes. Then decrease the pressure to 100 MPa at a rate of 0.5 MPa / s and hold for 5 minutes. Finally, release the pressure at a rate of 1 MPa / s. After demolding, the raw product is obtained with a density of 1.52 g / cm³.
[0086] 4) The raw product is loaded into the roasting tank and filled with filler with good thermal conductivity. Then it is loaded into the roasting furnace and purged with nitrogen gas to maintain a positive pressure of 0.5 kPa in the furnace. The temperature is then increased to 200℃ at a rate of 8.0℃ / h and held for 10h. The temperature is then increased to 900℃ at a rate of 5.0℃ / h and held for 20h. The temperature is then decreased to 80℃ at a rate of 6.0℃ / h and the pressure is released. After the furnace is opened and cooled to room temperature, the product is taken out of the roasting tank to obtain the first roasted product.
[0087] 5) After the product is preheated to 280°C after one firing, it is placed in an impregnation tank. The air inside the impregnation tank is evacuated and then liquid impregnation bitumen with a softening point of 80°C is injected for pressure impregnation. The maximum impregnation pressure is 2.0 MPa, and the impurity content of the impregnation bitumen used is <0.05%.
[0088] 6) After impregnation, the product is placed in a roasting furnace, covered with filler with good thermal conductivity, and heated to the maximum temperature of 800℃. The heating rate from room temperature to 400℃ is 8℃ / h, then it is held at 400℃ for 10h, the heating rate from 400℃ to 800℃ is 5℃ / h, and it is held at 800℃ for 15h. After that, it is naturally cooled to 100℃ and then removed from the furnace to obtain the second roasted product.
[0089] 7) The second-calcined product is loaded into the Atchison graphitization furnace and heated to 3000℃ for graphitization treatment. The heating rate is 20℃ / h to 500℃, 7℃ / h to 1500℃, 10℃ / h to 1800℃, 15℃ / h to 2400℃, and 20℃ / h to the highest temperature. During the heating process, Freon gas is introduced when the temperature reaches 1800℃ and is stopped when the temperature drops to 2200℃. Based on the weight of the product loaded into the furnace, the amount of gas introduced per ton of product is 25kg. After natural cooling to 200℃, the product is removed from the furnace, resulting in isostatic graphite with an internal impurity content of 260ppm, a porosity of 12.8%, a bulk density of 1.80g / cm³, a flexural strength of 59MPa, and an oxidation weight loss rate of 5.9%.
[0090] Comparative Example 2
[0091] The difference between Comparative Example 2 and Example 2 is that no high-temperature impurity removal treatment was performed on the primary coke powder. The other process steps and parameters, such as mixing, pressing, calcination, impregnation, and graphitization, remained consistent. The coke powder used in Comparative Example 2 had a median particle size (D50) of 5 μm, a loose packing density of 0.31 g / cm³, a tapped density of 0.63 g / cm³, and an impurity content of 0.48%. The resulting isostatic graphite had an internal impurity content of 350 ppm, a porosity of 7.7%, a bulk density of 1.87 g / cm³, a flexural strength of 67 MPa, and an oxidation weight loss rate of 4.5%.
[0092] Comparative Example 3
[0093] The difference between Comparative Example 3 and Example 3 is that no high-temperature impurity removal treatment was performed on the primary coke powder. The other process steps and parameters, such as mixing, pressing, calcination, impregnation, and graphitization, remained consistent. The coke powder used in Comparative Example 3 had a median particle size (D50) of 12 μm, a loose packing density of 0.40 g / cm³, a tapped density of 0.78 g / cm³, and an impurity content of 0.44%. The resulting high-purity isostatic graphite had an internal impurity content of 225 ppm, a porosity of 10.5%, a bulk density of 1.83 g / cm³, a flexural strength of 56 MPa, and an oxidation weight loss rate of 6.4%.
[0094] III. Product Testing and Result Analysis
[0095] The median particle size D50, loose density, tap density, impurity content, bulk density, flexural strength, impurity content, porosity, and oxidation weight loss (600℃, 30h) of coke powder, raw products, and isostatically pressed graphite products in each embodiment and comparative example were tested according to the testing methods and conditions specified in relevant national standards. The test results are shown in Table 1.
[0096] Table 1
[0097]
[0098] As can be seen from the test data in the various embodiments and comparative examples, the internal impurity content of the isostatic graphite produced by the present invention using refined coke powder is 12~18 ppm, which is much lower than that of the isostatic graphite produced by the conventional process in the comparative example (internal impurity content is 225~350 ppm). Furthermore, the isostatic graphite produced by the present invention using refined coke powder has other technical indicators such as bulk density, flexural strength, porosity, and oxidation weight loss rate that meet or exceed those of the comparative product.
[0099] Therefore, the overall performance of this invention has significant advantages compared to existing process technologies. This product is suitable for applications requiring high purity, such as solar photovoltaics, semiconductor crystal growth, electrical discharge machining, and new energy batteries.
[0100] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing refined coke powder, characterized in that, include: (1) Using calcined petroleum coke or calcined pitch coke as raw material, after crushing and grinding, coke primary powder with a particle size D50 of 5~25μm is obtained; (2) Add coke powder to a graphite crucible and then transfer it to a graphitization furnace for high-temperature halogen removal treatment; Heating is carried out by continuous heating, and the temperature is maintained at 2300~2500℃ for 2~6 hours, and then heating is stopped and the temperature is cooled down. During this process, Freon gas is continuously introduced when the temperature reaches 1800~1900℃, and the gas supply is stopped when the temperature drops to 2200℃. After cooling to room temperature, impurity-free coke powder with an impurity content of <0.01% is obtained. (3) The impurity-removed coke powder is fed into a fluidized bed air jet mill for dispersion, grinding and shaping; after air jet classification and magnetic separation, refined coke powder with D50 of 5~25μm is obtained.
2. The method according to claim 1, characterized in that, In step (1), the quality of calcined pitch coke or calcined petroleum coke should meet the following requirements: impurity content < 0.5%, volatile matter < 0.5%, sulfur content < 0.5%, and carbon content > 99.5%.
3. The method according to claim 1, characterized in that, In step (1), the raw material is first crushed to a particle size of less than 5 mm using a double roll crusher, and then the particles are ground using a vertical roller mill.
4. The method according to claim 1, characterized in that, In step (2), the heating rate of the graphitization furnace is 5~25℃ / hour.
5. The method according to claim 1, characterized in that, In step (2), the coke powder is weighed before loading into the furnace, and Freon is introduced at 0.2-0.8% of its weight.
6. The method according to claim 1, characterized in that, In step (2), after heating is stopped, the crucible is cooled to 150~200°C by natural cooling, then removed from the graphitization furnace and further cooled to room temperature by natural cooling.
7. The method according to claim 1, characterized in that, In step (3), the impurity-removed coke powder is first transported from the crucible to the storage bin for temporary storage using a negative pressure conveying system, and then transported to the fluidized bed air jet mill for air jet classification according to the feeding requirements.
8. The method according to claim 1, characterized in that, In step (3), a magnetic separation system is used for magnetic separation. The magnetic separation system is equipped with at least 3 stages of iron removers, and each stage of iron remover is composed of permanent magnets with a magnetic force of more than 12000GS.
9. A method for further preparing high-purity isostatic graphite from the refined coke powder obtained by the method according to any one of claims 1 to 8, characterized in that, include: (1) Take refined coke powder and high-temperature coal tar pitch with impurity content <0.05% in a weight ratio of 0.8~1.0:1.0~1.6; first add the refined coke powder to the carbon kneader and preheat it to 150°C, then add the melted high-temperature coal tar pitch, and obtain a paste by kneading; take out the paste, and obtain pressed powder by cooling, crushing, secondary grinding and sieving. (2) The powder is filled into the mold and pressed into shape by a cold isostatic press to obtain the raw product; the raw product is subjected to a first roasting, impregnation, second roasting and high temperature graphitization treatment to obtain high purity isostatic graphite with internal impurity content <20ppm.
10. The method according to claim 9, characterized in that, During the high-temperature graphitization process after secondary calcination, the maximum temperature of 2800~3000℃ is gradually reached in a stepped manner: the temperature is increased to 500℃ at a rate of 20℃ / h, to 1500℃ at a rate of 5~10℃ / h, to 1800℃ at a rate of 7~10℃ / h, to 2400℃ at a rate of 10~15℃ / h, and to the maximum temperature at a rate of 15~20℃ / h. When the temperature reaches 1800℃, Freon gas is introduced. Based on the weight of the product loaded into the furnace, the amount of gas introduced per ton of product is calculated to be 10~25kg. The gas introduction continues until the temperature drops to 2200℃ during the cooling phase.
Citation Information
Patent Citations
Preparation method of isotropic graphite material with superfine structure
CN116444274A
Preparation method of isotropic nuclear graphite
CN117024146A
Semiconductor graphite material and preparation method thereof
CN119430939A
Preparation method of high-energy density type artificial graphite cathode material
CN103456958A
Production method for isostatic pressure graphite
CN104591150A
Cited By
A system and method for preparing graphite material for isostatic pressing of sapphire
CN122343565A